IITA 50th anniversary conference - opportunities and threats driving the future of agriculture in Africa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Towards Food and Nutrition Security for the next Half Century: Challenges, Opportunities, and Strategies.